The application of an occupational therapy nutrition education programme for children who are obese. - Munguba MC; Valdés MTM; da Silva CAB (Occupational Therapy International, 2008)
The aim of this study was to evaluate an occupational therapy nutrition education programme for children who are obese with the use of two interactive games. A quasi-experimental study was carried out at a municipal school in Fortaleza, Brazil. A convenient sample of 200 children ages 8-10 years old participated in the study. Data collection comprised a semi-structured interview, direct and structured observation, and focus group, comparing two interactive games based on the food pyramid (video game and board game) used individually and then combined. Both play activities were efficient in the mediation of nutritional concepts, with a preference for the board game. In the learning strategies, intrinsic motivation and metacognition were analysed. The attention strategy was most applied at the video game. We concluded that both games promoted the learning of nutritional concepts. We confirmed the effectiveness of the simultaneous application of interactive games in an interdisciplinary health environment. It is recommended that a larger sample should be used in evaluating the effectiveness of play and video games in teaching healthy nutrition to children in a school setting. Copyright (c) 2008 John Wiley & Sons, Ltd.